Maternal Resveratrol Treatment Reduces the Risk of Mammary Carcinogenesis in Female Offspring Prenatally Exposure to 2,3,7,8-Tetrachlorodibenzo-p-Dioxin - de Lima e Silva, Tássia C. [UNESP]; da Silveira, Livia T. R. [UNESP]; Fragoso, Mariana F. [UNESP]; da Silva, Flávia R. M. [UNESP]; Martinez, Meire F. [UNESP]; Zapaterini, Joyce R. [UNESP]; Diniz, Odair H. G. [UNESP]; Scarano, Wellerson R. [UNESP]; Barbisan, Luis F. [UNESP] (Springer Nature, 2017)
2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) presents adverse effects on breast development/carcinogenesis. This study aimed to identify the ability of resveratrol (Res) to modify the adverse effects of TCDD in a female offspring. Pregnant female Wistar rats were allocated into four groups: TCDD, TCDD + Res, Res, and control. TCDD (1 μg/kg) was orally administered as a single dose on gestational day (GD) 15, and Res was orally administered during GD10–21 and lactation at a dose of 20 mg/kg/day. Female offsprings were euthanized on a specific postnatal day (PND) for hormonal analysis (PND 22, 48–51), vaginal opening (PND 30–48), and mammary gland morphology (PND 22). Other females received two doses of N-nitroso-N-methylurea (MNU, 50 mg/kg) on PNDs 22 and 51 and were euthanized on PND 24 (Ki-67, ER-α and apoptosis indexes or molecular analysis) or PND 180 (tumor assay). TCDD exposure altered the development of the mammary structure while these alterations were partially improved by maternal Res. Two days after first MNU administration, some genes associated with apoptosis were altered in the mammary tissue from the TCDD group (Bax and Caspase 3 down- and Bcl-2 upregulated) but were also partially reestablished by maternal Res. Mammary gland bcl-2 and bcl-xl proteins expression was increased while the apoptosis index was reduced by TCDD exposure but restored by maternal Res. An increase in number of mammary tumors was observed in female offspring from the TCDD group compared to the other groups. The results indicate that most mammary changes induced in female offspring through TCDD exposure or after MNU administrations were reduced by maternal resveratrol treatment.